Measurement of the B± Meson Nuclear Modification Factor in Pb-Pb Collisions at sNN =5.02 TeV - Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Bergauer, Thomas; Md. Ali, Mohd. Adli (American Physical Society, 2017)
The differential production cross sections of B mesons are measured via the exclusive decay channels B → J=ψK → μþμ−K as a function of transverse momentum in pp and Pb-Pb collisions at a centerof-mass energy ffiffiffiffiffiffiffiffi sNN p ¼ 5.02 TeV per nucleon pair with the CMS detector at the LHC. The ppðPb PbÞ data set used for this analysis corresponds to an integrated luminosity of 28.0 pb−1 (351 μb−1). The measurement is performed in the B meson transverse momentum range of 7 to 50 GeV=c, in the rapidity interval jyj < 2.4. In this kinematic range, a strong suppression of the production cross section by about a factor of 2 is observed in the Pb-Pb system in comparison to the expectation from pp reference data. These results are found to be roughly compatible with theoretical calculations incorporating beauty quark diffusion and energy loss in a quark-gluon plasma.